Pemasaran Kopi Gayo Melalui Sektor Pariwisata; Analisis Sosiologi Pilihan Rasional - Nurul Khansa Fauziyah; Shasa Chairunnisa; Aini Mahara; Nurul Hikmah (Indonesian Journal of Tourism and Leisure, 2023)
Before the COVID-19 pandemic, the tourism sector was the strongest sector in the world economy. The great strength of the tourism sector is proven by the rapid recovery of the sector after the COVID-19 pandemic. The tourism sector includes several things, including exhibitions, expos, and festivals. The purpose of this study was to find out how the rational thinking process of the Bener Meriah Regency government was used in choosing a sector for marketing Gayo coffee. This study used a qualitative approach with interview and observation techniques. The results of this study show that the tourism sector is one of the choices for the Bener Meriah Regency government in marketing Gayo coffee products. The tourism sector, in this case, is exhibition, expo, and festival activities. This activity is considered beneficial for Gayo coffee marketing because it can directly bring together coffee producers with tourists who are potential customers. Therefore, the Bener Meriah Regency government, taking into account (rational) resources and profits, chose the tourism sector to market Gayo coffee.